Low injury rates in elite athletes - Baxter-Jones, A. D.; Maffulli, N.; Helms, P. (Archives of Disease in Childhood, 1993)
A group of 453 elite young athletes (231 boys, 222 girls) in five two year age groups from 8-16 years of age was followed up for two years in order to identify self reported injuries over that period. Four sports were studied, namely football (soccer), gymnastics, tennis, and swimming. The injury rate was low with just over half the children suffering one or more injuries per year, with the majority of those injured sustaining one injury only. Over the two year period of intensive sporting activity this amounted to less than one injury per 1000 hours of training. The highest risk of injuries was in football (67%) and the lowest in swimming (37%). Most injuries (70%) were acute and of a minor nature, although overuse injuries did require longer periods off training and competition than acute injuries (20 v 13 days). Footballers appeared to sustain more significant injuries than other sports as judged by the time required to resume training and/or competition (16 days after acute and 57 after overuse). No significant associations were found between injury rate, injury severity, sex, and pubertal status with the single exception of female gymnasts in whom more injuries occurred in the latter stages of puberty. Only four of the 453 athletes reported injury as a reason for retiring from their chosen sports. Most injuries in elite young athletes are minor, their prevalence is low and, at least in the short to medium term, do not constitute a significant health problem.